Preparation method of beta-lactoglobulin fiber
The low-temperature plasma-assisted acid treatment method has solved the problem of low fiberization of milk protein fibers, improved their structural and functional properties, and has particularly great potential for application in food processing.
Patent Information
- Application Number
- CN202510896508.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-10-31
AI Technical Summary
The low degree of fiberization of existing milk protein fibers limits their application in the food processing field.
A low-temperature plasma-assisted acid treatment method was used to induce the aggregation of β-lactoglobulin molecules into fibrous structures through non-covalent interactions, thereby altering their surface chemical properties and enhancing the degree of fibrosis.
It increases the degree of fibrillation of milk protein fibers, enhancing their structural and functional properties, such as emulsifying activity, foaming ability, and antioxidant properties.
Smart Images

Figure CN120859095A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing β-lactoglobulin fibers, and more particularly to a method for preparing β-lactoglobulin fibers by low-temperature plasma-assisted acid treatment. Background Technology
[0002] Milk protein fibers possess unique structural features and high aspect ratios, demonstrating promising application potential as delivery carriers for fat-soluble functional factors. With their extremely high aspect ratio and various surface functionalities, protein fibers exhibit better amphiphilicity, foaming properties, and higher heat resistance compared to natural proteins, making them effective delivery carriers for water-insoluble bioactive compounds in food systems. A common preparation method for milk protein fibers involves heating at pH 2.0 for 10 hours, resulting in fibrous aggregates. However, the relatively low degree of fiberization in this method significantly limits its application in food processing. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing β-lactoglobulin fibers. This method effectively improves the degree of fibrillation during the preparation of milk protein fibers, resulting in β-lactoglobulin fibers with better structural and functional properties.
[0004] The technical solution of the present invention: a method for preparing β-lactoglobulin fibers, comprising the following steps: S1. Place a 10 mg / mL β-LG solution at room temperature and stir continuously with a magnetic stirrer for 2 h. Then store it at 4°C to complete the overnight hydration process and centrifuge to obtain product A. S2. Prepare a solution of product A with a certain concentration and add it to the plasma reactor; S3. Set the input voltage U of the plasma reactor, maintain the current within 1±0.002A, control the reaction temperature T, and the processing time t to obtain the finished product P-β-LGF.
[0005] In the aforementioned method for preparing β-lactoglobulin fibers, the S1 centrifugation operation is set with a relative centrifugal force of 4000 g and a duration of 20 min.
[0006] In the aforementioned method for preparing β-lactoglobulin fibers, the specific preparation method of the A-product solution in S2 is as follows: dissolve the A-product in an acidic solution and make the concentration of the A-product solution 1-20 mg / mL.
[0007] In the aforementioned method for preparing β-lactoglobulin fibers, the concentration of product A solution is 10 mg / mL.
[0008] In the aforementioned method for preparing β-lactoglobulin fibers, the input voltage U in step S3 is in the range of 40-80V.
[0009] In the aforementioned method for preparing β-lactoglobulin fibers, the input voltage U is 60 V.
[0010] In the aforementioned method for preparing β-lactoglobulin fibers, t is 40-120 s.
[0011] In the aforementioned method for preparing β-lactoglobulin fibers, t is 80s.
[0012] In the aforementioned method for preparing β-lactoglobulin fibers, the reaction temperature T is 24.5-25.5℃.
[0013] Compared with the prior art, the present invention has the following advantages: The present invention prepares β-lactoglobulin fibers by low-temperature plasma acid treatment. β-LG molecules aggregate together through non-covalent interactions to form a fiber structure. Compared with conventional acid treatment, the degree of fiberization is higher. Low-temperature plasma-assisted acid treatment can change the surface chemical properties of β-LGF and increase the surface hydrophilicity or lipophilicity, which may lead to enhanced interactions between fibers, thereby enabling fiber aggregation, resulting in better structural characteristics, while maintaining good functional characteristics. Attached Figure Description
[0014] Figure 1 This is a graph showing the particle size and potential measurement results of four products: P-β-LGF, β-LGF, U-β-LGF, and the original β-LGF. Figure 2 These are Fourier transform infrared spectra of the four products of this invention: P-β-LGF, β-LGF, U-β-LGF, and the original β-LG. Figure 3 These are fluorescence detection images of thioflavin dyes from four products: P-β-LGF, β-LGF, U-β-LGF, and the original β-LG. Figure 4 This invention relates to the circular dichroism chromatographic detection of four products: P-β-LGF, β-LGF, U-β-LGF, and the original β-LG. Figure 5 These are the antioxidant test charts for the four products of this invention: P-β-LGF, β-LGF, U-β-LGF, and the original β-LG. Figure 6 This is a comparative experimental diagram of the concentration of β-LG solution in the embodiments of the present invention; Figure 7 This is a comparative experimental diagram showing different plasma treatment times according to embodiments of the present invention; Figure 8 This is a comparative experimental diagram of different plasma processing powers in embodiments of the present invention. Detailed Implementation
[0015] The present invention will be further described below with reference to the accompanying drawings and embodiments, but this should not be construed as limiting the invention. The applicant has conducted a series of experiments, which demonstrate that the method provided by the present invention is effective and controllable, and can effectively improve the preparation efficiency of milk protein fibers.
[0016] Materials and reagents: β-LG (purity > 98%), trichloroacetic acid (purity > 99%, Shanghai Aladdin Reagent Co., Ltd.); ethylenediaminetetraacetic acid (purity > 99%, Sinopharm Chemical Reagent Co., Ltd.); 1,1-diphenyl-2-picrylhydrazine (DPPH) (purity > 97%, Sinopharm Chemical Reagent Co., Ltd.); other commonly used reagents were purchased from Shanghai Lingfeng Reagent Co., Ltd.
[0017] Example. A method for preparing β-lactoglobulin fibers, comprising the following steps: S1. Place a 10 mg / mL β-LG solution at room temperature and stir continuously with a magnetic stirrer for 2 h. Then store it at 4℃ to complete the overnight hydration process and centrifuge it. The centrifugation operation is performed with a relative centrifugal force of 4000 g for 20 min to obtain product A. S2. Dissolve product A in an acidic solution to prepare a 10 mg / mL product A solution, and add it to the plasma reactor; S3. Set the input voltage U of the plasma reactor to 60V, maintain the current within 1±0.002 A, control the reaction temperature T to (25.0±0.5)℃, and the processing time t to 80s to obtain the finished product P-β-LGF.
[0018] Comparative Example 1. A 10 mg / mL β-LG solution was placed at room temperature and stirred continuously with a magnetic stirrer for 2 h, then stored at 4 °C overnight for hydration. Centrifugation was performed at room temperature at a speed of 4000 g for 20 min, followed by adjusting the pH of the β-LG solution to 2.0 with 5.0 M HCl solution. The solution was then placed in a 90 °C water bath and reacted for 10 h. After the reaction was complete, the sample was cooled in an ice-water mixture for 30 min. β-LGF was finally obtained.
[0019] Comparative Example 2. A 10 mg / mL β-LG solution was placed at room temperature and stirred continuously with a magnetic stirrer for 2 h, then stored at 4°C to complete the overnight hydration process. Centrifugation was performed at room temperature at a speed of 4000 g to obtain product A. Product A was dissolved in an acidic solution to prepare a 10 mg / mL solution, which was added to the plasma reactor. The reaction was carried out for 20 min with an ultrasonic power of 30% for 30 min and an interval of 2 s to obtain U-β-LGF.
[0020] The four products obtained—P-β-LGF, β-LGF, U-β-LGF, and the original β-LGF—were subjected to structural and functional characterization analyses. Structural characterization included particle size and potential determination; Fourier transform infrared spectroscopy; thioflavin dye fluorescence detection; and circular dichroism spectroscopy. Functional characterization included emulsifying activity and stability determination; foaming ability and stability determination; and antioxidant activity testing.
[0021] Particle size and potential determination: The particle size and potential of four products—P-β-LGF, β-LGF, U-β-LGF, and the original β-LG—were determined using a Malvern laser particle size analyzer. DTS0012 and DTS1070 quartz cuvettes were used as sample cells. The samples were reconstituted with deionized water to a concentration of 1 mg / mL. The refractive index of the dispersant was set to 1.33, the refractive index of the protein particles to 1.46, and the test temperature to 25℃. After equilibration in the instrument for 120 s, the measurements were repeated three times.
[0022] As shown in the attached diagram of the instruction manual. Figure 1 As shown, P-β-LGF has the largest particle size and the highest potential level, proving that P-β-LGF has the advantages of high loading and high stability.
[0023] Fourier Transform Infrared Spectroscopy: Fourier transform infrared spectroscopy (FTIR) was performed using the potassium bromide pellet method. Four products—P-β-LGF, β-LGF, U-β-LGF, and the original β-LG—were mixed with potassium bromide at a ratio of 1:100 and then ground until homogeneous. Scanning conditions were set as follows: spectral range [range to be specified]. The number of scans was 32, and the resolution was [missing information]. Potassium bromide alone was used as a blank control.
[0024] The test results are shown in the attached diagram in the instruction manual. Figure 2 As shown, compared to the untreated sample, the OH / NH vibration absorption peak in the protein samples after acid treatment, ultrasonic-assisted acid treatment, and low-temperature plasma modification changed from the initial value. Shift towards lower frequency direction This phenomenon may be due to changes in the spatial conformation of proteins, which increase the number of hydrogen bonds. Furthermore, low-temperature plasma-assisted acid treatment makes the conformational changes of proteins more significant, further promoting the formation of hydrogen bonds.
[0025] Detection of thioflavone dye fluorescence: Accurately weigh 8 mg of thioflavone powder and dissolve it in 10 mL of phosphate buffer (containing 10 mM PBS, 150 mM NaCl, pH 7.0). After complete dissolution, filter sterilely through a 0.22 μm filter membrane, transfer to a brown bottle, seal, and store at 4°C in the dark for one week. Before testing, dilute the concentrated solution 50 times to prepare the ThT working solution. Then, mix 5 mL of the ThT working solution with 50 μL of the sample to be tested thoroughly, shake for 60 s, and detect using a fluorescence spectrophotometer. The instrument parameters were set as follows: 440 nm monochromatic light excitation, emission spectrum acquisition range 460-600 nm, excitation and emission slit widths both maintained at 10 nm, and spectral scan rate set to 1200 nm / min.
[0026] It can bind to the β-sheet structure in proteins and emit strong fluorescence, and can be used as an indicator of protein fibrillation. The stronger the ThT fluorescence intensity, the more protein fibrils are formed. The detection results are shown in the attached figure in the instruction manual. Figure 3 As shown, the P-β-LGF prepared in the example has the highest fluorescence intensity, indicating a good preparation effect.
[0027] Circular dichroism chromatography (CD) was used to detect four products: P-β-LGF, β-LGF, U-β-LGF, and the original β-LG. These products were dissolved in distilled water at pH 2.0 to achieve a final concentration of 0.2 mg / mL. During the CD analysis, the scanning wavelength range was set to 190–250 nm. The optical path length of the sample cell was set to 0.1 cm. The average of three scans was used as the experimental result.
[0028] The test results are shown in the attached diagram in the instruction manual. Figure 4 As shown, for the α-helix content, β-LG > P-β-LGF > β-LGF > U-β-LGF, with values of 10.4%, 9.6%, 9.2%, and 8.1%, respectively; for the β-sheet content, P-β-LG > U-β-LGF > β-LGF > β-LG, with values of 32.7%, 28.1%, 26.8%, and 25.9%, respectively. This indicates that the β-sheet content of all three treatments significantly increased compared to the original β-LG, with the most significant increase observed in the example.
[0029] Emulsifying activity and stability assays: 15 mL of protein dilutions of four products (P-β-LGF, β-LGF, U-β-LGF, and original β-LG) were weighed and placed in centrifuge tubes, and 5 mL of soybean oil was slowly added. The mixture was subjected to high-speed shearing at 12000 g for 1 min to obtain a homogeneous emulsion. At the 0 min and 10 min points, 50 μL of the emulsion sample was removed from the bottom and mixed with 3 mL of 0.1% (w / v) SDS solution. The absorbance was measured at 500 nm.
[0030] The Emulsifying Activity Index (EAI) is calculated using the following formula: The parameters in this formula are defined as follows: F corresponds to an oil phase ratio of 0.25 (volume fraction), and L is the optical path length of the cuvette (10). -2 m, C refers to protein concentration 10. -3 g / mL, the unit of emulsifying activity index is m² / g.
[0031] The formula for calculating the emulsification stability index is as follows:
[0032] The parameters in this formula are defined as follows: A0 represents the absorbance at 0 minutes, A10 represents the absorbance at 10 minutes, and the unit of emulsification stability index is _____.
[0033] Foaming ability and stability: 20 ml of the diluted protein solution was homogenized at 12,000 rpm for 60 s, and the initial volume was measured (labeled V1). After the sample was allowed to stand for 3 min, the final volume was measured again (labeled V2). Foaming characteristics were calculated using the following formula:
[0034] The parameters in this formula are defined as follows: V1 refers to the volume before mixing (mL), V2 refers to the immediate volume after mechanical treatment (mL), and V3 refers to the volume at the end of the settling stage (mL).
[0035] The test results are shown in Table 1. Table 1. Emulsifying activity, stability, foaming ability, and stability of four products: P-β-LGF, β-LGF, U-β-LGF, and the original β-LGF. Sample <![CDATA[EAI (m 2 / g)]]> ESI (min) FA (%) FS (%) β-LG <![CDATA[77.8±0.95 c ]]> <![CDATA[33.76±0.72 d ]]> <![CDATA[36.35±0.73 d ]]> <![CDATA[106.12±0.75 d ]]> β-LGF <![CDATA[87.32±1.12 a ]]> <![CDATA[36.86±0.28 c ]]> <![CDATA[74.75±0.52 b ]]> <![CDATA[135.42±0.82 b ]]> U-β-LGF <![CDATA[82.7±1.05 b ]]> <![CDATA[38.13±0.41 b ]]> <![CDATA[61.14±0.78 c ]]> <![CDATA[132.84±0.71 c ]]> P-β-LGF <![CDATA[86.58±0.74 a ]]> <![CDATA[40.64±0.56 a ]]> <![CDATA[95.22±0.47 a ]]> <![CDATA[141.3±0.98 a ]]> As shown in the table above, the products prepared in Experimental Example, Comparative Example 1, and Comparative Example 2 are all superior to the original β-LG. The fibrous morphology of the protein exhibits excellent interfacial activity, enabling rapid migration and adsorption at the oil-water interface. This results in a more stable emulsion system and foam. The fibrous structure provides a more effective protective layer for oil droplets, preventing droplet aggregation and stratification. The protective layer formed on the oil droplet surface may be more continuous and uniform, thereby improving the stability of the emulsion system and foam. The reason why the ultrasonically assisted acid-treated sample is lower than the acid-treated sample is that the ultrasonic-assisted acid treatment may generate local thermal effects, leading to thermal denaturation of the protein, which alters the structure of β-LGF, reducing the hydrophobic regions on the surface and weakening its adsorption efficiency at the oil-water interface. In contrast, during low-temperature plasma treatment, reactive oxygen species (ROS) and reactive nitrogen species (RNS) continuously act on the protein, fully exposing its internal hydrophobic groups and amino acid residues, strengthening the binding ability of the protein to oil droplets, and thus significantly improving the emulsification performance and foaming characteristics of the sample.
[0036] Antioxidant testing DPPH free radical scavenging experiment: Solutions of 0.5 mg / mL P-β-LGF, β-LGF, U-β-LGF, and the original β-LG product were accurately prepared and mixed thoroughly with an equal volume of DPPH ethanol working solution (0.1 mM). The mixture was reacted at room temperature for 60 min in the dark. The absorbance was measured at 517 nm using a UV-Vis spectrophotometer.
[0037] ABTS free radical scavenging experiment: A 7 mM ABTS aqueous solution was mixed with a 2.45 mM potassium persulfate aqueous solution and stored in the dark at 4°C for 12–16 h to prepare an ABTS stock solution. The stock solution was diluted with anhydrous ethanol to make the OD value of the ABTS test solution at 747 nm 0.70 ± 0.02. For testing, 0.5 mg / mL solutions of four products—LP-β-LGF, β-LGF, U-β-LGF, and the original β-LG—were mixed with the ABTS test solution at a volume ratio of 1:3. After standing in the dark for 1 h, the absorbance was measured at a wavelength of 734 nm.
[0038] Fe 2+ Reduction assay: 150 μL of 2 mmol / L FeCl2 was added to 1 mL of 10 mg / mL solutions of four products: LP-β-LGF, β-LGF, U-β-LGF, and the original β-LG. After rapid mixing, 200 μL of 5 mmol / L o-phenanthroline solution was added. The absorbance was measured after a colorimetric reaction at 562 nm for 10 min. Deionized water was used as a control instead of the modified protein sample.
[0039] The test results are shown in the attached diagram in the instruction manual. Figure 5As shown, Figure (A) corresponds to the results of the DPPH experiment, Figure (B) corresponds to the results of the ABTS experiment, and Figure (C) corresponds to the results of the Fe experiment. 2+ The results of the reduction experiment showed that the antioxidant properties of Example 1 and Comparative Example 1 were the highest.
[0040] In summary, the P-β-LGF prepared in the examples has good structural and functional properties. That is, when preparing β-lactoglobulin fibers, this application can effectively improve the degree of fibrinization of lactoglobulin while still maintaining good functional properties.
[0041] To further investigate the influence of some parameters in the embodiments on the preparation effect, this application further sets up comparative experiments on the concentration of the raw material β-LG solution, comparative experiments on different plasma treatment times, and comparative experiments on different plasma treatment powers, in order to seek the optimal treatment conditions.
[0042] Comparative experiment on the concentration of β-LG solution in raw materials: Based on the example, the concentration of β-LG solution in S1 was set to 1 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, and 20 mg / mL, while keeping other conditions unchanged. The fluorescence intensity was positively correlated with the amount of proteofibrous formation, as shown in the attached figure in the instruction manual. Figure 6 As shown, when the lactoglobulin concentration was 1 mg / mL, the ThT signal value was only 1443, which was at the detection baseline. As the concentration gradient increased to 10 mg / mL, the fluorescence response showed a continuous strengthening trend, eventually reaching a maximum signal intensity of 4856. However, the fluorescence intensity and protein concentration did not have a simple linear positive correlation. When the β-LG concentration was further increased to 15 mg / mL and 20 mg / mL, the excessively high protein concentration caused the ThT dye binding sites to reach saturation, at which point the fluorescence intensity no longer increased but instead decreased. Therefore, the preparation effect was best when the β-LG solution concentration was set to 10 mg / mL.
[0043] Comparative experiment of different plasma treatment times: Based on the example, the treatment time in S3 was set to 40s, 60s, 80s, 100s, and 120s, while keeping other conditions unchanged. The fluorescence intensity was positively correlated with the amount of proteofibrous tissue generated, as shown in the attached figure in the specification. Figure 7As shown, the ThT fluorescence signal of β-LG exhibits a significant nonlinear variation with treatment time. When the treatment time is 40-80 s, the ThT fluorescence intensity increases exponentially with increasing treatment time, reaching a peak of 4438 AU at 80 s, confirming that moderately extending the plasma treatment time can significantly promote the fibrillation efficiency of β-LG. However, when the treatment time exceeds the 80 s threshold, the fluorescence intensity shows an abnormal decay, indicating that the positive correlation between the degree of β-LG fibrillation and the plasma treatment time has a threshold (80 s). Further observation in the experiment revealed that excessively long treatment times (>80 s) induce arc discharge in the plasma system, causing a sharp increase in the temperature of the quartz medium and triggering thermal denaturation of β-LG. This structural damage interferes with the protein self-assembly process, ultimately inhibiting fibrillation formation and leading to a decrease in ThT fluorescence intensity.
[0044] Comparative experiment of different plasma treatment powers: Based on the example, the treatment power in S3 was set to 40s, 60s, 80s, 100s, and 120s, while keeping other conditions unchanged. In this application, the plasma treatment current remained constant; therefore, the treatment power was adjusted by regulating the voltage. The fluorescence was detected using a thioflavone dye fluorescence detection method, and the fluorescence intensity was positively correlated with the amount of proteofibrous tissue generated. The results are shown in the attached figures of the specification. Figure 8 As shown, within the power range of 40-60 W, the ThT fluorescence intensity of β-LG significantly increased with increasing treatment power, reaching a peak at 60 W. When the power was further increased to 70-80 W, the fluorescence intensity showed a significant decrease. This trend indicates that excessively high plasma treatment power is detrimental to the fibrillation process of β-LG. It is speculated that this is because high-intensity plasma treatment promotes the oxidation and molecular aggregation of β-LG, altering the original structural characteristics of the protein. This leads to irreversible changes in the native structure of β-LG. The structurally modified protein molecules are difficult to fully unfold during subsequent acid-thermal treatment, thus hindering the formation of ordered fibrils.
[0045] In summary, the optimal treatment conditions are a protein concentration of 10 mg / mL, a low-temperature plasma treatment time of 80 s, and a treatment power of 60 W.
Claims
1. A method for preparing β-lactoglobulin fibers, characterized in that: Includes the following steps: S1. Place a 10 mg / mL β-LG solution at room temperature and stir continuously with a magnetic stirrer for 2 h. Then store it at 4°C to complete the overnight hydration process and centrifuge to obtain product A. S2. Prepare a solution of product A with a certain concentration and add it to the plasma reactor; S3. Set the input voltage U of the plasma reactor, maintain the current within 1±0.002A, control the reaction temperature T, and the processing time t to obtain the finished product P-β-LGF.
2. The method for preparing β-lactoglobulin fibers according to claim 1, characterized in that, The S1 centrifugation operation is set with a relative centrifugal force of 4000 g and a duration of 20 min.
3. The method for preparing β-lactoglobulin fibers according to claim 1, characterized in that, The specific preparation method of the A-grade solution in S2 is as follows: dissolve the A-grade solution in an acidic solution to make the concentration of the A-grade solution 1-20 mg / mL.
4. The method for preparing β-lactoglobulin fibers according to claim 3, characterized in that, The concentration of the A-grade solution is 10 mg / mL.
5. The method for preparing β-lactoglobulin fibers according to claim 1, characterized in that, The input voltage U in S3 is in the range of 40-80 V.
6. The method for preparing β-lactoglobulin fibers according to claim 5, characterized in that, The input voltage U is 60 V.
7. The method for preparing β-lactoglobulin fibers according to claim 1, characterized in that, The t mentioned is 40-120s.
8. The method for preparing β-lactoglobulin fibers according to claim 7, characterized in that: The value of t is 80s.
9. The method for preparing β-lactoglobulin fibers according to claim 7, characterized in that: The reaction temperature T is 24.5-25.5℃.